EVALUASI PROSES AKUISISI BANK ABC TERHADAP PERFORMA BANK XYZ INDONESIA - , Muhammad Yasrie Akbar; , Dr. Fahmy Radhi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In 2009, super regional banks strategic plan was implemented by XYZ formed in 2007, with the process of acquisition of ABC bank's business in asia region, one of which is Indonesia. Mergers and acquisitions are the external growth strategy that is growth from outside the company, and is a fast way to access new markets for their products and time-saving process with significant internal growth. Business acquisitions of ABC is one of the major steps of XYZ to compete in Indonesia's banking market, this acquisition activities have a direct impact on the performance of XYZ Bank both financially and non-financially. In general, the performance of the Bank will acquire financially positive growth, but need to be further from the nonfinancial effects arising from the acquisition. The Study is to evaluate the acquisition process and also to find the supporting and the inhibiting factors to the acquisition process. Research method used is descriptive qualitative research with comparative methods by comparing two states before and after the event. Primary data was obtained through interviews directly against three Middle Top Management, while the secondary data was obtained from the annual report of the XYZ bank in the three years before and two years after acquisition. XYZ did the well the acquisition process, with a good overview plan and also well implemented from all management and staff. Generally the acquisition process did by XYZ for ABC, escpecially in Indonesia, was well implemented and this also gave the XYZ extra power to compete in Indonesiaâs Banking Industry. XYZ Indonesia succed in gaining more revenue after the acquisition compare to the time before the acquisition, those because the increase in business unit, but unfortunat ely the cost of XYZ Indonesia also got increased and drop the effectiveness. Several factors have been identified as a supporting factors, which are the commitment of the management of XYZ Indonesia, and XYZ financial capabilities as major capital centers.